Health-related quality scores in childhood interstitial lung disease: Good agreement between patient and caregiver reports - Griese, Matthias; Schwerk, Nicolaus; Carlens, Julia; Wetzke, Martin; Emiralioglu, Nagehan; Kiper, Nural; Marczak, Honorata; Lange, Joanna; Krenke, Katarzyna; Ullmann, Nicola; Krikovszky, Dora; Hämmerling, Susanne Hedwig; et al. (Pediatric pulmonology, 2024)
Introduction Childhood interstitial lung disease (chILD) is a heterogeneous group of mostly chronic respiratory disorders. Assessment of health-related quality of life (HrQoL) in chILD has become increasingly important in clinical care and research. The aim of this study was to assess differences between patient-reported (self) and caregiver-reported (proxy) HrQoL scores. Methods This study used data obtained from the chILD-EU Register. After inclusion (baseline), the patient's health status was followed up at predefined study visits. At each study visit, caregivers and patients were handed validated, age-specific HrQoL questionnaires. HrQoL data entered at baseline were used to compare self- and proxy-reported HrQoL scores. For the longitudinal analysis, we compared HrQoL scores between the baseline and the next follow-up visit. Results No differences between patient- and caregiver-reported HrQoL scores were found for school functioning, chILD-specific questionnaire score, and physical health summary score. Self-reported HrQoL scores were higher for the subscales emotional functioning (77.4 vs. 70.7; p < .001), social functioning (81.9 vs. 76.2; p < .001), as well as psycho-social summary score (76.5 vs. 71.8; p < .001) and total score (74.7 vs. 70.8; <.001). The longitudinal analysis showed that a significant change in a patient-reported HrQoL score resulted in a significant change in a caregiver-reported HrQoL score after a mean time of 11.0 months (SD 9.4). Conclusions We found a good agreement between children- and caregiver-related HrQoL scores. In chILD, caregivers are able to sense changes in children's HrQoL scores over time and may be used as a proxy for children unable to complete HrQoL questionnaires.
Online veröffentlicht: 5. Juni 2024
Gesehen am 22.01.2025